Nontuberculous mycobacteria in the environment of Hranice Abyss, the world's deepest flooded cave (Hranice karst, Czech Republic) - Pavlik, Ivo; Gersl, Milan; Bartos, Milan; Ulmann, Vit; Kaucka, Petra; Caha, Jan; Unc, Adrian; Hubelova, Dana; Konecny, Ondrej; Modra, Helena (Environmental science and pollution research international, 2018)
Nontuberculous mycobacteria (NTM) are widely distributed in the environment. On one hand, they are opportunistic pathogens for humans and animals, and on the other hand, they are effective in biodegradation of some persistent pollutants. Following the recently recorded large abundance of NTM in extreme geothermal environments, the aim of the study was to ascertain the occurrence of NTM in the extreme environment of the water zone of the Hranice Abyss (HA). The HA mineral water is acidic, with large concentrations of free CO2, and bacterial slimes creating characteristic mucilaginous formations. Both culture and molecular methods were used to compare the mycobacterial diversity across the linked but distinct ecosystems of HA and the adjacent Zbrašov Aragonite Caves (ZAC) with consideration of their pathogenic relevance. Six slowly growing NTM species (M. arupense, M. avium, M. florentinum, M. gordonae, M. intracellulare) and two rapidly growing NTM species (M. mucogenicum, M. sediminis) were identified in the water and in the dry zones at both sites. Proteobacteria were dominant in all the samples from both the HA and the ZAC. The bacterial microbiomes of the HA mineral water and HA slime were similar, but both differed from the microbiome in the ZAC mineral water. Actinobacteria, a phylum containing mycobacteria, was identified in all the samples at low proportional abundance. The majority of the detected NTM species belong among environmental opportunistic pathogens.
Keywords: Environmental saprophytic mycobacteria; Česká republika; Epidemiology; Caves; Water Microbiology; netuberkulózní mykobakterie; Inorganic carbon; mikrobiologie vody; Cave bacterial slimes; Czech Republic; Nontuberculous Mycobacteria; Geomycobacteriology; Environmental Monitoring; monitorování životního prostředí; jeskyně